Effects of different daytime exercises on the quality of sleep and appetite of obese women - Khadijeh Irandoust; Morteza Taheri (International Archives of Health Sciences, 2018)
Aims: The aim of this study was to determine the effects of daytime aerobic exercise on the subsequent sleep and appetite of obese women. Materials and Methods: It was a semi-experimental study with pre and post-test design. Fifteen obese women were asked to do aerobic exercises three sessions a week for 2 weeks, with each session lasting 60 min at 60% of maximum heart rate either at 9:00 am or 18:00 pm. A body composition analyzer (InBody-320, South Korea) was used to measure weight, fat percentage, and body mass index (BMI). Nocturnal sleep–wake schedule data and sleep patterns in the two conditions (morning vs. evening) were recorded at 1-min intervals and scored with the Actiwatch Sleep Analysis 8 software. Paired t-test and independent t-test were used to analyze the data. Results: Results (age, 46.9 ± 5.2 years; BMI, 33.6 ± 3.2 kg/m2; and percentage of body fat ≥35%) showed that sleep efficiency, wake bouts, actual sleep, and sleep latency were improved after exercise training (P ≤ 0.05). Furthermore, morning exercise condition resulted in a better improvement in sleep efficiency (73.41% ± 6.94%), wake bouts (15.81% ± 3.30%), and sleep latency (79.47% ± 6.09%) compared to that of evening exercise (P ≤ 0.05). It was also reported that the perceived satiety was not significantly different in the two conditions (P = 0.94 and P = 0.076, respectively, for morning and evening), while the perceived hungry was improved significantly in the morning condition (P = 0.003). Conclusion: As a result, aerobic exercises at the time of the morning can lead to a better quality of sleep and decline in hungry of obese women compared to the evening exercise.